An impact of radiation on laminar flow of dusty ternary nanofluid over porous stretching/shrinking sheet with mass transpiration - Mahabaleshwar, U. S.; Maranna, T.; Perez, L. M.; Bognar, G. V.; Öztop, Hakan Fehmi (Elsevier, 2023)
The goal of current research is to determine the laminar boundary layer problem for the two-dimensional flow of ternary dusty nanoparticles through a porous stretching/shrinking sheet in the presence of radiation and mass transpiration. Generalized partial differential equations are converted to nonlinear ordinary differential equations after demonstrating an appropriate similarity transformation. Exact solutions are subsequently provided for the resulting system of equations. The development of ternary dusty nanofluids has significantly improved the heat transmission process for manufacturing and industrial applications, as well as in nanotechnology research. The influence of the various interesting parameters on the flow and heat transfer is analyzed and discussed in detail through plotted graphs. It was found that the basic similarity equations admit two phases for both stretching/shrinking surfaces. Graphs are used to illustrate the findings of this work. We found that the velocity fields increase with an increase in the inverse Darcy number value for the case stretching sheet while opposite effects can be observed in the shrinking case. Moreover, the magnitude of particle interaction parameter enhances as the solution domain raises. The findings disclose that the performance of ternary nanofluid phase heat transfer is improved compared to dusty phase performance.
Keywords: Dusty fluids; Ternary nanofluid; Radiation; ODE; Porous media; Mass suction; injection